Dispersion of Iron Nanoparticles by Polymer-Based Hybrid Material for Reduction of Hexavalent Chromium. (15th November 2015) - Ali, Syed Wasim; Mirza, Mumammad Latif; Bhatti, Tariq M.; Naeem, Kashif; Imran Din, Muhammad
Abstract : A gel type acrylic acid resin, based on ethyl acrylate-co-1, 7-octadiene, has been synthesized by suspension polymerization at 20% cross-linking and subsequent hydrolysis by H2 SO4 . Capacity of the resin was observed to be 8.90 meq/g or 3.28 meq/mL. The iron nanoparticles used in this study were synthesized by ferrous sulphate method by using LiBH4 as a reductant and characterized by SEM, TEM, XRD, surface area, and electrical properties. Later, the resin was applied for the dispersion of iron nanoparticles over its surface for the reduction of Cr(VI) and subsequent adsorption of Fe(III) and Cr(III) as byproducts. In the column studies the reduction of Cr(VI) and the adsorption of Cr(III) and Fe(III) have been observed up to 240 μ mole/L.